FIT2 proteins and lipid droplet emergence, an interplay between phospholipid synthesis, surface tension, and membrane curvature - Graff, Juliette; Schneiter, Roger (Frontiers in Cell and Developmental Biology, 2024)
The intracellular storage of metabolic energy in lipid droplets (LDs) is a fundamental process vital for cellular homeostasis. Understanding the intricate mechanisms governing LD biogenesis has gained significant attention due to their implications in prevalent metabolic disorders such as type 2 diabetes and obesity. Among the proteins involved, Fat storage-Inducing Transmembrane 2 (FIT2) stands out for its pivotal role in LD formation. FIT2 influences the emergence step of LD biogenesis, as in FIT2 mutant cells LDs remain embedded within the endoplasmic reticulum (ER) membrane instead of properly emerging into the cytosol. While in vitro studies have demonstrated FIT2's ability to bind diand triacylglycerol (DAG/TAG) and cleave acyl-CoA, the translation of these functions to the observed LD embedding in FIT2 deficient cells remains to be fully elucidated. This article seeks to narrow this gap by reviewing FIT2's role in LD emergence. We highlight the factors affecting LD emergence, particularly focusing on membrane curvature, surface tension, and lipid composition, and their interplay with FIT2. Additionally, we explore hypotheses proposing how FIT2 may locally modulate lipids at sites of LD emergence, shedding light on its intricate function within cellular lipid metabolism.